Controlled surface mineralization of metal oxides on nanofibers1. Issue 47 (27th May 2015) - Horzum, Nesrin; Mari, Margherita; Wagner, Manfred; Fortunato, Giuseppino; Popa, Ana-Maria; Demir, Mustafa M.; Landfester, Katharina; Crespy, Daniel; Muñoz-Espí, Rafael
<x xml:space="preserve">Abstract</x> Metal oxide/polymer hybrid nanofibers are prepared by in situ formation of metal oxide nanoparticles on surface-functionalized polymer fibers.